2018
DOI: 10.5194/isprs-archives-xlii-4-w10-89-2018
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal for an Improved Transportation Model in Citygml

Abstract: <p><strong>Abstract.</strong> CityGML, an OGC standard, is an open data model for virtual 3D city models and includes buildings, roads, terrain, water bodies, etc. While many modules are well-developed (eg buildings, bridges, tunnels), the transportation model is, based on our consultations with various government agencies and municipalities, not sufficient for most transportation applications. We propose in this paper several improvements to the CityGML v2.0 Transportation module, and to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…This information is typically used (and required) in navigation systems and traffic simulations (cf. Ruhdorfer et al 2018;Labetski et al 2018). According to Labetski et al (2018) also Waterway was introduced as new subclass of TransportationSpace.…”
Section: Transportation Modulementioning
confidence: 99%
See 1 more Smart Citation
“…This information is typically used (and required) in navigation systems and traffic simulations (cf. Ruhdorfer et al 2018;Labetski et al 2018). According to Labetski et al (2018) also Waterway was introduced as new subclass of TransportationSpace.…”
Section: Transportation Modulementioning
confidence: 99%
“…Ruhdorfer et al 2018;Labetski et al 2018). According to Labetski et al (2018) also Waterway was introduced as new subclass of TransportationSpace. In addition, the new class Marking allows for adding road markings to the road surface and the classes Hole and HoleSurface can be used to represent, for instance, roadway damages or manholes including their surfaces.…”
Section: Transportation Modulementioning
confidence: 99%
“…Devys [17] discussed interoperability, between the RailTopoModel [81] and Land-Infra, for railway infrastructure and proposed a mapping between the two models. Labetski et al [39] analysed the usage of LandInfra as a framework for extending the definition of the LODs for roads in the transportation module of CityGML, but found that the lack of the concept of levels of detail in LandInfra made it irrelevant. [49] also propose to analyse LandInfra in the context of roads but for the purpose of determining limitations in current data standards for road assets and create recommendations towards an improved standard in order to apply SW (Semantic Web) technologies to build a prototype solution for road asset data conflation.…”
Section: Landinfra (And Infragml) In Theory and Practicementioning
confidence: 99%
“…Among those papers, the majority of them discuss the relationship between LandInfra and the ISO 19152 LADM (Land Administration Domain Model) [11][12][13][14][15][16]. There are also several papers examining the applicability of LandInfra for extending the transportation modelling of roads [17] in the context of road asset management [18][19][20], and for the interoperability between the LandInfra and RailTopoModel [21] for railway infrastructure [22]. Others discuss the usability of LandInfra (& InfraGML) in specific use cases, such as in the creation of a tax valuation information model [15], underground utility network modelling [23] and possible alignments [24] with the CityGML Utility Networks ADE [25] and PipelineML [26], environmental acoustic studies [27], and modelling legal interests and legal boundaries [28].…”
Section: Landinfra and Infragmlmentioning
confidence: 99%
“…Within asset management, the maintenance of roads and transportation networks is key to keeping traffic moving smoothly and safely on a daily basis. Road maintenance includes activities such as smoothness control/de-icing, repairs, closures, milestone maintenance and traffic city furniture replacement [17].…”
Section: Asset Managementmentioning
confidence: 99%